2018
DOI: 10.3171/2017.11.jns171738
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of cerebral aneurysm persistence and occlusion after flow diversion: a single-institution series of 445 cases with angiographic follow-up

Abstract: OBJECTIVEFlow diversion requires neointimal stent overgrowth to deliver aneurysm occlusion. The existing literature on aneurysm occlusion is limited by heterogeneous follow-up, variable antiplatelet regimens, noninvasive imaging modalities, and nonstandard occlusion assessment. Using a large, single-center cohort with low attrition and standardized antiplatelet tapering, the authors evaluated outcomes after flow diversion of anterior circulation aneurysms to identify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
72
4
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 92 publications
(87 citation statements)
references
References 43 publications
6
72
4
5
Order By: Relevance
“…Further analysis revealed that at 12 months, adjunctive coiling predicted occlusion, whereas male sex, aneurysm size and incorporation of a branch vessel predicted aneurysm persistence. Prior treatments, vessel of origin, fusiform morphology and number of devices used did not predict aneurysm occlusion 39…”
Section: Treatment Optionsmentioning
confidence: 88%
See 2 more Smart Citations
“…Further analysis revealed that at 12 months, adjunctive coiling predicted occlusion, whereas male sex, aneurysm size and incorporation of a branch vessel predicted aneurysm persistence. Prior treatments, vessel of origin, fusiform morphology and number of devices used did not predict aneurysm occlusion 39…”
Section: Treatment Optionsmentioning
confidence: 88%
“…Open microsurgery lends to immediate dome occlusion but may be fraught with high morbidity 45 46 48 51 52. In contrast, conventional endovascular treatment with endosaccular coil embolisation is associated with known risks of recurrence, whereas parent vessel remodelling through flow diversion with delayed complete aneurysm occlusion can lead to aneurysm growth 39 53. Additionally, a curative result from flow diversion treatment of the more fusiform and supergiant aneurysms becomes limited given the challenges of achieving endothelialisation along a longer length of device construct without a wall.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We are hyper-vigilant in these cases, waiting a full 30 min post-embolization for final control angiography prior to ending the case. Siddiqui et al shared the case of a patient with a giant MCA aneurysm treated with flow diversion and dense coil packing in which the patient experienced acute post-procedural stent thrombosis and cautioned against densely packing the aneurysm with coils 24. We also use a light coil pack (14% packing density overall) and systemically heparinize these patients overnight following their procedure, all to limit the risk of acute stent thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…The Pipeline embolization device (PED) was approved with a similar indication for large and giant aneurysms of the internal carotid artery (ICA). The PED has low rates of major complication and complete occlusion of ∼80% of aneurysms 1 year after treatment, in creasing thereafter [3-5]. Recanalization and recurrence after coiling as well as aneurysm persistence after flow diversion (FD) are a problem in spite of these contemporary technologies [6].…”
Section: Introductionmentioning
confidence: 99%